Pengembangan e-Modul berbasis Canva pada Mata Kuliah Manajemen Kelas di Institut Agama Islam Ibrahimy Genteng Banyuwangi - Musyarofah, Atiqatul; Zahro, Sliviatus (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2024)
In the digital era, students – who are Generation Z – have the skills to operate smartphones and use the internet to search for information. Therefore, learning media is very important to support independent learning and help learning activities in the classroom. This research aims to develop an e-module that provides materials and discussion materials in PDF format that are easily accessible in classroom management courses. This study is a research and development (R&D) study. The results of the e-module practicality test using the Canva application in the classroom management course of classroom setting material at the Ibrahimy Genteng Islamic Institute Banyuwangi by semester VI students showed very practical results with a total percentage of 85.2%. The indicators of the practicality of the e-module include aspects of appearance, presentation of materials, and benefits, where each aspect gets a percentage above 82.1% in the very practical category